Yield and Quality of Some Tropical Sugarbeet Genotypes Under Bangladesh Conditions (Bangladesh Agronomy Journal, 2022)
The experiment was conducted at the experimental farm of Agronomy and Farming Systems Division, Bangladesh Sugarcrop Research Institute (BSRI), Ishurdi, Pabna, Bangladesh during 2012-13 cropping season to assess the comparative performance of yield and quality of six tropical sugarbeet genotypes viz., CS 0327, HI 0473, CS 0328, HI 0044, Shubhra and Cauvery. The different genotypes showed significant differences in their yield and yield components, such as beet length, beet girth, beet yield, shoot yield, sugar yield and harvest index. The quality parameters, such as total soluble solids or brix, sucrose percentage and apparent purity percentage of sugarbeet were also different among the genotypes. Maximum beet length (31.38 cm), beet girth (36.09 cm), beet yield (75.46 t ha-1), shoot yield (38.46 t ha-1) and sugar yield (11.82 t ha-1) were found in Cauvery followed by CS 0328. In case of sugarbeet quality, the maximum total soluble solids (TSS) and sucrose percentage (21.90% and 15.68%, respectively) were recorded in Cauvery followed by the genotype CS 0328 (21.52% and 15.50%, respectively). So, it was concluded that tropical sugarbeet genotype Cauvery appeared as the best one with respect to yield and quality parameters followed by CS 0328 under Bangladesh conditions.Bangladesh Agron. J. 2021, 24(2): 55-61